Chronic postsurgical pain in children and young adults with cancer and choice of regional anesthesia for amputation and limb‐sparing surgery. Issue 2 (7th October 2022) - Anghelescu, Doralina L.; Johns, Emma; Bhatia, Shalini; Frett, Michael J.; Lu, Zhaohua
Abstract: Background: Patients undergoing limb amputation (LA) or limb‐sparing (LS) for lower extremity oncologic diagnoses are at similar risk for chronic postsurgical pain of neuropathic nature (CPSP/NP). Regional anesthesia (RA) techniques are pre‐emptive measures to prevent the occurrence of the CPS/NP. However, recommendations for epidural (EP) versus peripheral nerve blocks (PNBs) lack in pediatric literature. Aims: This study investigates the incidence and duration of CPSP/NP and describes NP‐directed regimens. Methods and Results: Data on demographics, use of EP or PNB, duration of CPSP/NP, and NP‐directed medication were retrospectively collected for LA and LS between 2009 and 2019. Mixed effects logistic regression was used to compare the odds of CPSP/NP between EP and PNB. Cox PH model with adjustment for clustering due to multiple surgeries on patients was used to quantify rate of pain relief between surgery groups (LA vs. LS) and RA groups (EP vs. PNB). The incidence of CPSP/NP was 36 (23.8%) after 165 surgeries (150 patients). The odds of CPSP/NP after PNB were 2.5 times those of CPSP/NP after EP ( p = .11). The rate of pain relief at any instant after the EP was 1.2 times that after PNB ( p = .3). The rate of pain relief for LS with EP was 1.9 times that of pain relief for LA with EP, a statistically significant difference ( p = .03). Gabapentin was used (94.5%), with addition of amitriptyline (24.2%) and both amitriptyline and methadone (12.7%). Conclusion: The LS with the EP group had a significantly higher rate of relief of CPSP/NP than LA with EP. Odds of CPSP/NP after PNB were 2.5 times those of CPSP after EP.